Nanotechnology research directions for societal needs in 2020 retrospective and outlook - Roco, Mihail C; Mirkin, Chad A.; Hersam, Mark C. (Science policy reports, 2011)
This volume presents a comprehensive perspective on the global scientific, technological, and societal impact of nanotechnology since 2000, and explores the opportunities and research directions in the next decade to 2020.  The vision for the future of nanotechnology presented here draws on scientific insights from U.S. experts in the field, examinations of lessons learned, and international perspectives shared by participants from 35 countries in a series of high-level workshops organized by Mike Roco of the National Science Foundation (NSF), along with a team of American co-hosts that includes Chad Mirkin, Mark Hersam, Evelyn Hu, and several other eminent U.S. scientists.  The study performed in support of the U.S. National Nanotechnology Initiative (NNI) aims to redefine the R&D goals for nanoscale science and engineering integration and to establish nanotechnology as a general-purpose technology in the next decade. It intends to provide decision makers in academia, industry, and government with a nanotechnology community perspective of productive and responsible paths forward for nanotechnology R&D. Nanotechnology Research Directions for Societal Needs in 2020 is a wonderful piece of work. This book reflects the bible for nanotechnology for the next decades for the whole world.  Well done.  (Prof. Marcel van de Voorde, Delft University of Technology, Delft, November 2010) "This book provides a comprehensive vision and an overarching roadmap for the nanotechnology community. It comes at a great time as we move into the next decade of nano-enabled commercialization."  (Vincent Caprio, Executive Director, NanoBusiness Commercialization Association, November 2010). The National Nanotechnology Initiative story could provide a useful case study for newer research efforts into fields such as synthetic biology, renewable energy or adaptation to climate change.  (David Rejeski, Woodrow Wilson International Center for Scholars, September 2010) Some of these [nanotechnology] research goals will take 20 or more years to achieve. But that is why there is such a critical role for the federal government. (President Bill Clinton, Speech announcing NNI at Caltech, January